Where's my Roy Cohn? [videorecording (DVD)] - Auletta, Ken; Cohn, Roy M.; Roiphe, Anne Richardson, 1935- (2019)
Roy Cohn was a ruthless and unscrupulous lawyer and political power broker whose 28-year career ranged from acting as chief counsel to Senator Joseph McCarthy's Communist-hunting subcommittee to molding the career of a young Queens real estate developer named Donald Trump.